2011
DOI: 10.1093/jxb/err063
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the role of climacteric ethylene in kiwifruit (Actinidia chinensis) ripening using a 1-aminocyclopropane-1-carboxylic acid oxidase knockdown line

Abstract: During climacteric fruit ripening, autocatalytic (Type II) ethylene production initiates a transcriptional cascade that controls the production of many important fruit quality traits including flavour production and softening. The last step in ethylene biosynthesis is the conversion of 1-aminocyclopropane-1-carboxylic acid (ACC) to ethylene by the enzyme ACC oxidase (ACO). Ten independent kiwifruit (Actinidia chinensis) lines were generated targeting suppression of fruit ripening-related ACO genes and the frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(105 citation statements)
references
References 73 publications
5
89
0
1
Order By: Relevance
“…The application of exogenous ethylene or its analogue propylene accelerates the ripening of kiwifruit in four main phases, as hypothesized by Atkinson et al (2011) and Schröder and Atkinson (2006), and as shown in Figure 6. Phase I is the pre-climacteric (unripe) stage characterized by high firmness, high TA, and low SSC, making kiwifruit unsuitable for consumption.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The application of exogenous ethylene or its analogue propylene accelerates the ripening of kiwifruit in four main phases, as hypothesized by Atkinson et al (2011) and Schröder and Atkinson (2006), and as shown in Figure 6. Phase I is the pre-climacteric (unripe) stage characterized by high firmness, high TA, and low SSC, making kiwifruit unsuitable for consumption.…”
Section: Introductionmentioning
confidence: 56%
“…Atkinson et al (2011) proposed a model of kiwifruit ripening induced by exogenous ethylene (see continuous lines in Fig. 6).…”
Section: Effects Of Propylene and 1-mcp Treatments On Kiwifruit Ripeningmentioning
confidence: 99%
“…The microarray expression analysis of a transgenic apple line in which MdACO1 was silenced led to the identification of 17 candidate genes that are likely to be ethylene control points for aroma production in apple [76]. Fruits of this line and fruits of a kiwifruit (Actinidia chinensis) line in which the AcACO1 gene was suppressed [77], presented a phenotype analogous to that described previously in apple [75].…”
Section: Metabolic Engineering Of Amino Acid-derived Volatiles In Fruitsmentioning
confidence: 62%
“…also identified nine gene models in the 'Hongyang' predicted coding sequence database for ACC oxidase. The AcACO1/AcACO3 and AcACO4/AcACO6 genes previously identified by Atkinson et al (2011) in 'Hort16A' clustered in pairs, whilst AcACO5 was more distantly related. The additional 'Hongyang' ACO gene models clustered with genes from tomato.…”
Section: Ethylene Biosynthetic Genesmentioning
confidence: 84%
“…Suppression of ethylene biosynthetic genes has been a powerful tool in identifying ethylene-controlled traits linked to ripening in tomato, apple, melon and kiwifruit (Oeller et al 1991;Schaffer et al 2007;Pech et al 2008;Atkinson et al 2011). In apple, a model for control of ripening was developed showing that individual ripening characters differ in their sensitivity to ethylene and dependency on ethylene.…”
Section: Ethylene Biosynthetic Genesmentioning
confidence: 99%